The Effect of Library Anxiety Handling Strategies on Visiting Interest of Librarians at The University of Sari Mutiara Indonesia Library - Harefa, Hilda Syaf'aini; Halawa, Kerisman; Katili, Ade Yul Pascasari (Library of Sultan Agung Islamic University, 2026)
This quantitative study investigates the impact of library anxiety management strategies on librarians’ visiting interest at the Sari Mutiara University Library Unit. Using random sampling of 98 respondents and regression-based analysis, the results demonstrate a positive and significant effect, confirming the strategic role of anxiety management in enhancing library engagement. The implications of this study reveals the implementation of appropriate library anxiety management strategies can increase users' comfort and confidence, thus increasing their interest in visiting the Sari Mutiara Indonesia University Library. This finding emphasizes the importance of strengthening orientation programs, providing supportive librarian services, and assisting with library facility use to encourage optimal library utilization. This research contribution strengthens the understanding of the role of library anxiety management strategies as an important factor influencing user interest in visiting. This finding adds empirical evidence to the field of library science and forms the basis for developing more effective and user-friendly services at the Sari Mutiara Indonesia University Library.Keywords : Management Strategy; Library Anxiety; Visitor Interest